Around the World with Irving Fisher - Thorvaldur Gylfason; Helgi Tómasson; Gylfi Zoega (Center for Economic Studies and ifo Institute (CESifo), 2015)
This paper aims to show why Irving Fisher's own data on interest rates and inflation in New York, London, Paris, Berlin, Calcutta, and Tokyo from 1825 to 1927 suggested to him that nominal interest rates adjusted neither quickly nor fully to changes in inflation, not even in the long run. In Fisher's data, interest rates have more persistence than inflation and change less than inflation over time. The Fisher effect is a misnomer unless it is taken to refer to what Fisher actually found and what his data show: a persistent negative effect of increased inflation on real interest rates.
Keywords: E31; E43; 330; Fisher effect; inflation; interest rates